1995
DOI: 10.1111/j.1365-2826.1995.tb00675.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear and Cytoplasmic Triiodothyronine‐Binding Sites in Primary Sensory Neurons and Schwann Cells: Radioautographic Study During Development

Abstract: The effects of the thyroid hormones on target cells are mediated through nuclear T3 receptors. In the peripheral nervous system, nuclear T3 receptors were previously detected with the monoclonal antibody 2B3 mAb in all the primary sensory neurons throughout neuronal life and in peripheral glia at the perinatal period only (Eur. J. Neurosci. 5, 319, 1993). To determine whether these nuclear T3 receptors correspond to functional ones able to bind T3, cryostat sections and in vitro cell cultures of dorsal root ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Schwann cells express a nuclear triiodothyronine receptor (NT 3 R). By autoradiography we demonstrated that the immuno-TRa-common (a1 and a2) detected NT 3 R corresponds to a specific [125I ]-labeled T 3 binding site (39)(40)(41). Since both sensory neurons and Schwann cells At embryonic stages ( E17-E21), TRa-common was weakly possess functional T 3 receptors, the present study was designed expressed by DRG cells (Fig.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Schwann cells express a nuclear triiodothyronine receptor (NT 3 R). By autoradiography we demonstrated that the immuno-TRa-common (a1 and a2) detected NT 3 R corresponds to a specific [125I ]-labeled T 3 binding site (39)(40)(41). Since both sensory neurons and Schwann cells At embryonic stages ( E17-E21), TRa-common was weakly possess functional T 3 receptors, the present study was designed expressed by DRG cells (Fig.…”
Section: Introductionmentioning
confidence: 76%
“…receptors and by the correlation between distribution of NT 3 R in which non neuronal cells were eliminated. Also T 3 stimulates the neurite outgrowth of sensory neurons in DRG explant cul-immunoreactivity and T 3 binding capacity (38)(39)(40)(41). tures.…”
Section: Introductionmentioning
confidence: 99%
“…Both sensory neurons and peripheral glial cells in dorsal root ganglia have been shown to possess specific T 3 binding sites (Walter & Droz, 1995). During development, sensory neurons express TRβ rather than TRα and the amount of TRβ positive neurons increased during the postnatal stages and remained stable in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, thyroid hormones and TSH could be able to affect the synaptic contacts of these ganglia cells. In this regard, the presence of TRs has been described in neurons and glia cells of the dorsal root ganglia and sciatic nerve of postnatal rats (45). The presence of TRs and TSHR in the smooth musculature and corpus cavernosum of the clitoris, as well as in the glial cells of the dorsal nerve of the clitoris has not been previously approached in any species.…”
Section: Discussionmentioning
confidence: 96%